Function Modeling in Engineering Design: Approaches and Methods - Mohammed, Osamah Malik; Shammari, Ahmed Z.M. (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Function modeling in engineering design, as one of the most common abstract language during design process and especially early stages, is introduced in a common frame for investigating possible development areas. Comparative studies are conducted for analyzing commonalities of various approaches and methods as well as its variances. The interaction of functional modeling with design theories and methodologies are reviewed in detail. The aims of those reviews are highlighting features of various methods of FM and its noticed limitations and discussing applicability of those methods and approaches in various fields of design. Finally, a proposed future works is presented for filling identified gaps within generality and applicability of FM within various design fields.